Pengaruh Pertumbuhan Ekonomi, Inflasi, dan Pengeluaran Pemerintah terhadap Kemiskinan di Kota Tasikmalaya pada tahun 2007-2020 - Rifka Amanda Fadillah; Dewi Rahmi; Westi Riani (UNISBA Press, 2022)
Abstract. The problem of this research is the city of Tasikmalaya which has the highest poverty rate among other regions and has the title of the poorest city in West Java. Poverty is influenced by several factors, namely the economic growth of the City of Tasikmalaya, which tends to increase, has not been evenly distributed, as a result of its economic contribution to the community and this city is also the result of the expansion that should be with high economic growth and then reduce poverty, but poverty in this city is still high, although In terms of inflation, this city is the lowest in West Java, and on the realization side of Government Expenditures in this city, which fluctuates, it is not necessarily spread effectively. The purpose of this study is to analyze the effect of economic growth, inflation and government spending on poverty levels in Tasikmalaya City. The data used is secondary data. The method used is regression analysis, descriptive analysis and time series data analysis. The results showed that economic growth and inflation had no significant effect on poverty, while government spending had a significant effect on poverty. Abstrak. Terdapat dua tujuan dari penelitian skripsi ini pertama, untuk menganalisis pengaruh pertumbuhan ekonomi , inflasi dan pengeluaran pemerintah terhadap tingkat kemiskinan di Kota Tasikmalaya. Kedua, untuk menganalisis besarnya pengaruh pertumbuhan ekonomi , inflasi dan pengeluaran pemerintah terhadap tingkat kemiskinan di Kota Tasikmalaya. Untuk mencapai tujuan tersebut penelitian ini menggunakan metode yang digunakan yaitu metode ekonometrika dengan analisis regresi, analisis deskriptif dan analisis data timeseries. Hasil penelitian bahwa pertumbuhan ekonomi dan inflasi tidak berpengaruh signifikan terhadap kemiskinan sedangkan pengeluaran pemerintah berpengaruh signifikan terhadap kemiskinan.